2013
DOI: 10.2105/ajph.2012.300874
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Network Factors Associated With Prevalent Hepatitis C Infection Among Rural Appalachian Injection Drug Users

Abstract: Objectives We determined the factors associated with hepatitis C (HCV) infection among rural Appalachian drug users. Methods This study included 394 injection drug users (IDUs) participating in a study of social networks and infectious disease risk in Appalachian Kentucky. Trained staff conducted HCV, HIV, and herpes simplex-2 virus (HSV-2) testing, and an interviewer-administered questionnaire measured self-reported risk behaviors and sociometric network characteristics. Results The prevalence of HCV infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
165
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 148 publications
(177 citation statements)
references
References 62 publications
7
165
5
Order By: Relevance
“…Although the magnitude of the outbreak was alarming, the introduction of HIV into a rural community in the United States was not unexpected when considered in the context of increasing trends in injection use of prescription opioid analgesics 1,4,7,9,11,14,34 and the new and steady rise in acute HCV infections in rural areas, particularly central Appalachia. 15 In addition, although approximately 50% of the persons who inject drugs in the United States are estimated to live outside major metropolitan areas, only an estimated 5.8% of syringes were exchanged in rural locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the magnitude of the outbreak was alarming, the introduction of HIV into a rural community in the United States was not unexpected when considered in the context of increasing trends in injection use of prescription opioid analgesics 1,4,7,9,11,14,34 and the new and steady rise in acute HCV infections in rural areas, particularly central Appalachia. 15 In addition, although approximately 50% of the persons who inject drugs in the United States are estimated to live outside major metropolitan areas, only an estimated 5.8% of syringes were exchanged in rural locations.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Hepatitis C virus (HCV) is the most common infection transmitted through drug injection, and a large proportion of new HCV infections are associated with injection-drug use. [9][10][11][12][13] In the United States, the number of cases of acute HCV infection reported from 2010 through 2013 increased by 151%, 10 and these increases have occurred disproportionately among young persons, 30 years of age or younger, who reside in nonurban areas 14 east of the Mississippi River, particularly within central Appalachia. 15 These communities have also historically had a very low prevalence of human immunodeficiency virus (HIV) infection.…”
mentioning
confidence: 99%
“…Furthermore, injection drug use is not uncommon in certain rural areas, and self-reported HCV prevalence among rural IDUs in eastern Kentucky was found to be elevated relative to non-IDUs, just as it is in urban centers (Havens et al, 2007). In fact, a recent study among rural drug users found the prevalence of HCV antibodies in 392 rural IDUs to be 54.6% (Havens et al, 2013), strikingly higher than the estimated prevalence of 1.6% for the U.S. population as a whole (Armstrong et al, 2006). Among the HCV-seropositive participants, only 31.2% were aware of their status (Havens et al, 2013).…”
Section: T He Continued Spread Of Hepatitis C Virusmentioning
confidence: 99%
“…In fact, a recent study among rural drug users found the prevalence of HCV antibodies in 392 rural IDUs to be 54.6% (Havens et al, 2013), strikingly higher than the estimated prevalence of 1.6% for the U.S. population as a whole (Armstrong et al, 2006). Among the HCV-seropositive participants, only 31.2% were aware of their status (Havens et al, 2013). Although the presence of antibodies does not always imply ongoing infection, several studies have found the risk of developing chronic disease following exposure to HCV to be substantially elevated in both injecting and noninjecting drug users relative to nonusers (Grebely et al, 2007;Page et al, 2009;Poustchi et al, 2011).…”
Section: T He Continued Spread Of Hepatitis C Virusmentioning
confidence: 99%
“…Prescription opioid injecting has been associated with increased incidence (Bruneau, Roy, Arruda, Zang, & Jutras-Aswad, 2012) and prevalence of HCV infection (Hadland, et al, 2014;Havens, et al, 2013;Havens, Walker, & Leukefeld, 2007;Zibbell, Hart-Malloy, Barry, Fan, & Flanigan, 2014). The injecting of prescription opioids has increased considerably over the past two decades in North America (Fischer & Argento, 2012;Jordan, Blackburn, Des Jarlais, & Hagan, 2017;B.…”
Section: Epidemiology and Prevention Of Hcv Infection Among Pwidmentioning
confidence: 99%